Domestic Violence Survivorship Among a Sample of Older African American Women: An Interpretative Phenomenological Analysis - Burse, Jacqueline (Journal of interpersonal violence, 2022)
African American women experience domestic violence at a rate that is 35% higher than the domestic violence rate of White women. Moreover, African American women encompass 8% of the US population but account for 22% of domestic violence?related homicide victims. African American women are at greater risk for facing economic difficulties, homelessness, unemployment, and health and educational disparities due to domestic violence. However, little attention has been given to the lived experiences of older women who are domestic violence survivors. Theories of phenomenology and hermeneutics provided the theoretical framework for this study. An interpretative phenomenological analysis framework guided the research design and data analysis process. Overall, the findings pointed toward the need for generating more culturally sensitive and culturally tailored programs and services to address domestic violence in the African American community. Additionally, services are needed that include faith-based education, training, and prevention programs to enable churches and social workers to address the unique cultural needs of African American women who have endured domestic violence.